Oxidation pond and aerated lagoon. - Suki , A.; Awang , M. (1990)
Oxidation ponds and aerated lagoon is a popular treatment method for sewage due to the ease of operation and maintenance. In Malaysia the design of these systems are based mainly on loading rates or retention time. No attempt have been made to design based on the kinetics or reactor type. Though the performance of the oxidation pond is expected to satisfy the Malaysian discharge standard A and B, studies carried out does not support this assumption. Actual monitoring data on several sewage treatments show an efficiency ranging from 32 to 89% for oxidation ponds and 70 to 91% for an aerated lagoon. Data also reveal that shortcircuiting occurs in the pond thus reducing its efficiency.